On the residual ionospheric error in radio occultation measurements. Issue 8 (10th August 2017) - Coleman, Christopher J.; Forte, Biagio
Abstract: The residual ionospheric error (RIE) in radio occultation (RO) measurement analysis is investigated through both analytic and numerical ray tracing. The study has shown that the difference between the propagation paths at different frequencies is an extremely important factor in determining the level of the RIE. Further, that horizontal ionospheric structure, such as the equatorial anomaly, can have a substantial impact. The results confirm the conclusion of previous studies that asymmetry in the ionosphere between the upward and downward legs of the propagation is a significant factor. The study has also considered the effect of traveling ionospheric disturbances upon the RIE. It has been shown that there can be dramatic changes in RIE through the full period of a traveling ionospheric disturbance (TID). Consequently, because of their frequency and unpredictability, TIDs have the potential to set a limit on the achievable accuracy of RO measurement analysis. Key Points: A complete simulating environment was prepared to model the propagation of radio occultation signals through ionized and neutral atmospheres Ray tracing used to model residual ionospheric error in the presence of realistic ionospheric structures under various conditions The presence of realistic ionospheric structures (e.g., TID) can set a limit on the achievable accuracy of RO measurements